Sirach and its contexts: the pursuit of wisdom and human flourishing - Adams, Samuel L.; Goering, Greg Schmidt; Goff, Matthew J. (Journal for the study of Judaism / Supplements, 2021)
"In Sirach and Its Contexts an international cohort of experts on the book of Sirach locate this second-century BCE Jewish wisdom text in its various contexts: literary, historical, philosophical, textual, cultural, and political. First compiled by a Jewish sage around 185 BCE, this instruction enjoyed a vibrant ongoing reception history through the middle ages up to the present, resulting in a multiform textual tradition as it has been written, rewritten, transmitted, and studied. Sirach was not composed as a book in the modern sense but rather as an ongoing stream of tradition. Heretofore studied largely in confessional settings as part of the Deuterocanonical literature, this volume brings together essays that take a broadly humanistic approach, in order to understand what an ancient wisdom text can teach us about the pursuit of wisdom and human flourishing"--